Indonesia's future business leaders: An analysis of MBA Student personality - Moore, Richard W; Mamun, Nurhayati (Jurnal Manajemen Teknologi, 2005)
What kind of business leaders will Indonesian MBA student become? Are Indonesian MBA students likely to be entrepreneurial leaders of more bureaucratic leaders? Will they managers who are self-motivated with a strong sense of self efficacy or will they wait for others to take that lead? Will today’s students be able to tolerate and even thrive in an increasingly complex and uncertain world, or will they prefer more structured and secure environments. The answer to these questions lies, in part, in the personality characteristics of the MBA students. Over the past fifty years researchers have developed a number measures for assessing managers’ personalities and studied the impact of the personality dimensions on managerial behavior (Whetten and Cameron, 2002). Most of this work has been done in United States and Europe, a few studies have been done in Asia, and we could find no studies specific to Indonesia. This article reports on an exploratory studu in which we describe the personality measures. We compare these student’s results with populations form the United States, to understand if Indonesian students are systematically different from the Americans in earlier studies and to identify implications for their future managerial style. Finally, we analyze MBA Student’s characteristics including, enrollment in the Executive program, gender and age to see if there are significant differences among Indonesian MBA students on these dimensions.